Design and development of latex cups collector robot (mechanical) - Khor, Xi Bo (2022)

(untitled)
Due to the growing demand, the products coming from rubber plantations, such as gloves, tires, and mattresses, are highly sought after. However, due to several factors, world rubber production has reduced in recent years, especially in Malaysia. In this project, an automated prototype robot for collecting latex cups was built to help workers in the latex collection process. This robot is constructed on a mobile platform based on a rear-wheel drive, double wishbone suspension, and Ackermann’s steering transmission, with a motor-driven Four Degree of Freedom (DoF) manipulator arm and a latex storage tank located on the platform. For the movement of the robot transmission and manipulator arm, ultrasonic sensors and a camera are employed to locate the position of rubber trees and latex cups, respectively. The Arduino Uno and the motor driver circuit are used as the controllers of this robot. The developed prototype robot has undergone prototype test runs to verify the control system, as well as the robot's mobility test, static test, and balance test, and to test the stability of the robot platform. Those results showed that the prototype design is feasible and is able to perform basic tasks automatically in the unstructured terrain of the rubber plantation. In addition, this prototype can act as a basic design for future development.